Abortion Due to Unwanted Pregnancy: Perspective of Islamic Law and Positive Law - Firdaus Firdaus; Jumni Nelly; Elimartati Elimartati; Hamdani Hamdani (Institut Agama Islam Negeri Kerinci, 2021)
This article is intended to look at the variants of the legal implications of abortion, both from the perspective of Islamic law and positive law in Indonesia. This research uses a juridical-normative approach which is based on the laws and regulations and the fatwas of ulama. The results showed that abortion can be classified into two, namely abortion for medical reasons and abortion not for medical reasons. Legally, abortion for medical reasons and performed by a doctor with integrity is a justified act. Both Islamic law and positive law in Indonesia justify this action by meeting certain conditions. The act of abortion that is not accompanied by medical indications is a prohibited act in Islamic law and positive law at the same time. This research is expected to contribute in completing the assessment of the variant of abortion in terms of Islamic law and positive law. However, this research needs to be continued by considering quantitative data on abortion, so that the resulting legal opinion is truly oriented towards the general benefit.